An Evening with Governor Brown and Jane Tolmach (1976)
This flyer invites supporters to a buffet reception on October 9, 1976, at the Oxnard Community Center honoring Jane Tolmach, Democratic candidate for State Assembly. The event features Governor Edmund G. Brown, Jr. as a special guest and serves as a campaign fundraiser, with donations set at $15 for individuals and $25 for couples. The invitation includes ticket purchase details and contact information for the Jane Tolmach for Assembly Committee.